On surfaces endowed with a canonical principal direction in Euclidean 4-spaces - Kelleci, Alev; Turgay, Nurettin Cenk; Ergut, Mahmut (Tubitak Scientific & Technological Research Council Turkey, 2019)
In this paper, we introduce canonical principal direction (CPD) submanifolds with higher codimension in Euclidean spaces. Then we obtain a classification of surfaces endowed with CPD relative to a fixed direction in Euclidean 4-space.
Keywords: Euclidean spaces; canonical principal direction; angle function